The Effect of Collaborative Learning Model Assisted by Flashcard On EFL Students’ Mastery of English Tenses - Siti Nur Aisyah; Sabarun; Hesty Widiastuty (Tamilis Synex: Multidimensional Collaboration, 2024)
This study aimed to measure the effect of the collaborative learning model assisted by flashcard on EFL students’ mastery of english tenses at SMP IT HASANKA Boarding School Palangka Raya. The research was quantitative research with Quasi-experimental design. The researcher designed the lesson plan, conducted the treatment, and counted the students’ scores by pre-test and post-test. The population of this research was all of the students of SMP IT HASANKA Boarding School, and the sample of this research was 45 students from class VIIIC as the experiment class and class VIIIB as the control class. The sample was determined using cluster sampling technique. The study concluded that teaching students' english tenses using a collaborative learning model assisted by flashcards was more effective than teaching using a textbook only. It was shown that the result of pre-test and post-test. The result of the T-test (2-tailed) generated was = 0.00 < 0.05. It can be seen that the sig. value was smaller than 0.05, meaning there is a significant effect on the collaborative learning model assisted by flashcards on student mastery of english tenses.